TRADISI BANGSA ARAB PRA-ISLAM DAN NILAI-NILAI AL-QUR'AN - Siti Ruqoiyah (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
This study tries to reveal the positive traditions of pre-Islamic Arabs confirmed by the Qur'an, by performing stages and filters in selecting these good traditions by approaching them through three interactions: tahmil, taghyir, tahrim. The method used in this research is descriptive analytical with a historical-sociological approach. The results of this study are positive traditions confirmed by the Qur'an are traditions whose substance does not conflict with three principles, namely: monotheism, equality, and fitrah insaniyah. Traditions included in this category are traditions in the form of tahmil, namely traditions that are accepted, perfected, and continued. Tradition that contains these values ​​and confirmed by the Qur'an is an individual tradition that is found in the nature of being honest, generous, fulfilling promises, being brave, patient, honoring guests, and being loyal. These positive traits are still being continued today